The Role of Social Support on Subjective Well-Being in Adolescents - Wanda Wahyu Anisa; Michael Geraldo; Erik Wijaya (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
This study aims to explore the role of social support on adolescents' subjective well-being. Social support is one of the important aspects that contribute to individual happiness, especially in the context of adolescent life, which often faces various emotional challenges. This study aims to determine the extent to which social support affects subjective well-being in adolescents. The research was conducted through an online survey involving 300 adolescent participants. The sampling technique used was purposive sampling, with data analysis conducted using linear regression. The results showed that social support contributed 36.5% to subjective well-being (R² = 0.365, p = 0.000). This finding indicates that the higher the social support received by individuals, the better their subjective well-being. Social support from friends and family has been shown to be effective in reducing stress and increasing happiness. This study concludes that social support has a significant influence on adolescents' subjective well-being, indicating the importance of positive social relationships in improving their quality of life.